2019
DOI: 10.1002/tcr.201800195
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Oceanic Waste Biomass: A Catalytic Perspective

Abstract: Efficacious waste utilization is vital in context of sustainability. The past decade has witnessed attempts of usage of land biomass and wastes for various applications, contributing towards a sustainable society. Exploitation of the marine biomass, which does not compete with habitation and food production like land biomass has been largely unnoticed and therefore not being utilized judiciously. Researchers have mainly exploited these resources as functional materials having significant potential applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 151 publications
0
7
0
Order By: Relevance
“…The transformation of chitin into various chemicals and the aspects of shell biorefinery have been previously addressed in a limited number of earlier reviews and perspectives. [8][9][10][11][12][13][14][15][16][17][18][19] While a few reviews have provided detailed descriptions of various aspects of shell waste valorization and offered insights into the potential of chitin valorization, the majority of other reviews have focused on specific areas, such as the synthesis of one particular category of chemicals. Notably, a comprehensive compilation and discussion on recent advancements in catalytic transformations of chitin biomass is conspicuously absent in the existing literature.…”
Section: Neha Ghoshmentioning
confidence: 99%
“…The transformation of chitin into various chemicals and the aspects of shell biorefinery have been previously addressed in a limited number of earlier reviews and perspectives. [8][9][10][11][12][13][14][15][16][17][18][19] While a few reviews have provided detailed descriptions of various aspects of shell waste valorization and offered insights into the potential of chitin valorization, the majority of other reviews have focused on specific areas, such as the synthesis of one particular category of chemicals. Notably, a comprehensive compilation and discussion on recent advancements in catalytic transformations of chitin biomass is conspicuously absent in the existing literature.…”
Section: Neha Ghoshmentioning
confidence: 99%
“…Research on indirect liquification process demonstrated the feasibility of two stage liquification, including thermochemical gasification followed by Fischer-Tropsch (F-T) process. This process is utilized for producing high biogenic biofuels from waste materials and shows potential to obtain high quality biofuel from agriculture biomass [ 90 ]. Single and multistage hydrolysis-fermentation processes were developed to produce ethanol from lignocellulose biomass, which do not require pretreatment or external enzyme addition, and demonstrate promising results in terms of process efficiency [ 91 ].…”
Section: Technologies For Conversion To Biofuelsmentioning
confidence: 99%
“…Extensive literature is reported on cellulose and hemicellulose-based biofuels and chemicals as well as lignin chemistry including waste biorefinery (Bhaskar et al 2020 ). Biopolymers of cellulose type, chitin and chitosan, marine algae, among other biogenic material waste can be converted advantageously to biofuels, energy products and biochemicals including niche applications in catalysis and biomedical industry (Bhaskar et al 2020 ; Colmenares et al 2017 ; Iravani and Varma 2020 ; Lucas et al 2019 ).…”
Section: The Quest For Sustainable Alternatives To Crude Oilmentioning
confidence: 99%